Theoretical Evaluation of Ultrasonic Velocities in Quanternary Systems - Baluja, Shipra; Karia, falguni (Asian Journal of Chemistry, 2010)
Ultrasonic velocity and densities of quaternary systems: chloroform-1,4-dioxane-toluene-cyclohexanone. chloroform-1,4- dioxane-toluene-hexane and chloroform-1,4-dioxane-toluene-heptane have been measured at 298 K as a function of concentration and these experimental values are compared with theoretical values evaluated by using various theories such as Flory Auerback, Nomoto, Van Deal-Vangeal, Rao's specific velocity, collision factor and impedance dependence. The relative applicability of these theories to the present systems has been checked and the results are explained in terms of molecular interactions occurring in these systems.